Design and implementation of an electronic goniometer for gait analysis - Adel, C.; Benabid, Y.; Louar, M. A. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Walking is the main mean of movement for Man, therefore in the last century many studies have been carried out to reach a better understanding the human walk. The study of this latter is multidisciplinary and, from a biomechanical point of view, it is based on records of the kinematics and dynamics of the different body segments set in motion (Neelesh et al. 2009). Motion capture devices are used in medical application to help practitioners in the clinical interventions and to improve performance of athletes, and in the analysis of the subject gait to evaluate the condition of the joints and bones (Yazdifar et al. 2013). Gait analysis aims to measure the angular variations of the body joints, mainly those of the lower limbs :the hip, the knee and the ankle (Neelesh et al. 2009). A functional implant or prosthesis requires an understanding of the basic mechanics of motion and load transfer which should be reflected in the implant design (Link and Keller 2003). Traditional goniometers are clinically used to measure joint angles, for example the maximum knee angle flexion/extension achieved by a patient under treatment (Yazdifar et al. 2013). This paper describes the design and realization of a system for recording real-time angles measurements (hip, knee and ankle) obtained on the basis of electronic goniometers for the lower limbs for the sagittal plane, intended for the North African population (Anthropometric measures: segment length, weight, height … etc.) by following and developing an appropriate and methodological design process. The identification and adaptation of appropriate tools and environments for the process design is proposed in order to improve the gait evaluation as a first step, and the design of medical devices as a second step.